A bibliometric analysis of global research output on health and human rights (1900-2017) - Waleed M. Sweileh (BMC, 2018)
Abstract Background Baseline data on global research activity on health and human rights (HHR) needs to be assessed and analyzed to identify research gaps and to prioritize funding and research agendas. Therefore, the aim of this study was to assess the growth of publications and research pattern on HHR. Methods A bibliometric methodology was used. Literature on HHR was retrieved using SciVerse Scopus for the study period from 1900 to 2017. Nine different search scenarios with different keyword combinations were used to retrieve the required documents. All types of documents published in peer-reviewed journals, including editorials, were included. The search strategy was validated. Results In total 6513 documents were retrieved with an h-index of 88 and an average of 9.8 citations per document. Publications on HHR field started as early as 1950 but showed a steep rise in the past two decades. Visualization of author keywords revealed that HIV/ AIDS, mental health, maternal and reproductive health, violence, ethics, torture, and refugees were most commonly encountered keywords. The journal "Health and Human Rights" was most active (n = 467; 7.2%) in this field. However, documents that appeared in The Lancet received the highest impact (29.5 citations per document). The United States of America produced the most in this field (n = 1817; 27.9%). Researchers in the region of Americas participated in approximately 45% of the retrieved documents while researchers in the Eastern Mediterranean region had the least contribution (2.5%). Researchers in high-income countries contributed to approximately 78% of the retrieved documents while researchers in low-income countries contributed to less than 5% of the retrieved documents. When data were standardized by population size, the research output from high-income countries was approximately four documents per one million inhabitants. For middle-income countries, the research output was 0.3 document per one million inhabitants. For low-income countries, the research output was 0.5 document per one million inhabitants. Conclusions Differential research productivity on HHR was seen among scholars in different world regions. World countries need to encourage and strengthen research on HHR in order to achieve the goals set in international agreements of human rights.